The Effectiveness of Cursory Reading Technique to Increase the Second Grade Student's Reading Comprehension - Musdalifah Ifah Rahman (Universitas Muhammadiyah Enrekang, 2020)
This research consisted of two objectives research, first objective research that was to find out whether or not the use of the cursory reading technique is effective to increase the reading comprehension of students, and second objective research that was to find out whether or not the interested of students in learning reading comprehension by using cursory reading technique. This research applied a quasiexperimental design, and cluster random sampling technique. The population of this research that was the second grade students of SMA Muhammadiyah Kalosi Enrekang regency. The sample of this research consisted of 72 students which divided two groups (experimental and control group). Research instruments were used to collect the data of reading comprehension in this research those are reading test and questionnaire. The result of the students’ reading comprehension in this research explained that the experimental group increased significantly. Moreover, based on the students’ response on questionnaire showed that the mean score of interest was 75.00 and it was categorized as interested.